Customised Simulation Tool For The Industrial Propane Dehydrogenation Reactor - Chin, S. Y.; Haniif, Prasetiawan; Anwaruddin, Hisyam; Abdullah, Azahari; Ikmal Hisham, Maharon (2014)
Modeling and simulation of the propane dehydrogenation reaction is important for predicting an optimum operating condition to maximize the propylene yield. The present study performed the modeling and simulation study of propane dehydrogenation over a platinum based catalyst in radial moving bed reactor (RMBR). First order power law model was used to express the propane dehydrogenation reaction and side reactions. RMBR was discretized into axial and radial directions and the equations of the discretized bed were solved numerically. The kinetic parameters were optimized by comparing the simulation results with plant data. The predicted propane conversion, reactor outlet temperature and coke content deviated less than 5% from the plant data. A user friendly graphical user interface (GUI) was developed based on the validated model. GUI can be used easily by the plant personnel for the RMBR simulation. The sensitivity studies were performed to evaluate the inﬂuence of different possible disturbances on the process. It was found that the reactor inlet temperature and H2/HC molar ratio were the most influential parameter to the reactor performance. The maximum propylene yield 30.34% was produced when the WAIT was +10 K, H2/HC was -0.2 and Us was +100 kg/hr from the base case.